The Union and the states : a study in fiscal federalism - Sharma, Jagdish Narayan (New Delhi : Sterling Publishers, 1974)
The purpose of the study is to assess and analyse how far the inter-governmental fiscal relations have been smooth and self-propelling; and if they have been otherwise what are the factors responsible for the stresses and strains
Includes index.
Bibliography: p. [236]-244.
osc 09/10/2019
Loans
Keywords: Intergovernmental fiscal relations